2021
DOI: 10.3390/foods10071572
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nutritional Quality Traits of a Common Bean Germplasm Collection

Abstract: Food legumes are at the crossroads of many societal challenges that involve agriculture, such as climate change and food sustainability and security. In this context, pulses have a crucial role in the development of plant-based diets, as they represent a very good source of nutritional components and improve soil fertility, such as by nitrogen fixation through symbiosis with rhizobia. The main contribution to promotion of food legumes in agroecosystems will come from plant breeding, which is guaranteed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 105 publications
2
17
0
Order By: Relevance
“…The significant 72 11485, 15109, 13315, 11350, 15106, 14109, 8035, 7399, 7028, 13757 G × E interaction for most of the traits indicated the sensitivity of nutrients accumulation to the environment. This suggests for further evaluation of the germplasm in multiple locations and multiple years to have a better insight into the G × E interaction existing for the traits (Murube et al, 2021) and selection thereafter. Low G × E interaction and moderate-tohigh heritability for most of the traits studied suggest a better selection response.…”
Section: Discussionmentioning
confidence: 99%
“…The significant 72 11485, 15109, 13315, 11350, 15106, 14109, 8035, 7399, 7028, 13757 G × E interaction for most of the traits indicated the sensitivity of nutrients accumulation to the environment. This suggests for further evaluation of the germplasm in multiple locations and multiple years to have a better insight into the G × E interaction existing for the traits (Murube et al, 2021) and selection thereafter. Low G × E interaction and moderate-tohigh heritability for most of the traits studied suggest a better selection response.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation for micronutrient concentration has been well studied in legumes ( Table 1 ). Research on legume crops have revealed significant genetic variations for the essential micronutrients in chickpea ( Ray et al, 2014 ; Jha et al, 2015 ; Rezaei et al, 2016 ; Vandemark et al, 2018 ; Karaca et al, 2020 ), common bean ( Beebe et al, 2000 ; Ray et al, 2014 ; Murube et al, 2021 ), cowpea ( Gerrano et al, 2022 ; Sodedji et al, 2022 ), lentil ( Ray et al, 2014 ; Kumar et al, 2016 ; Vandemark et al, 2018 ), mung bean ( Dahiya et al, 2013 ; Kumar and Pandey, 2020 ), Pea ( Ray et al, 2014 ; Jha et al, 2015 ; Dissanayaka, 2019 ; Klein et al, 2020 ) and soybean ( Kumar and Pandey, 2020 ). The promising genotypes identified can be utilized in biofortification programs for mapping studies and development of breeding material rich in micronutrients.…”
Section: Genetic Variation For Micronutrient Content In Legume Germplasmmentioning
confidence: 99%
“…Pulses and common bean ( Phaseolus vulgaris L.) in particular, play a key role in the traditional diets, in less developed countries of the world ( Murube et al, 2021 ; Singh et al, 2021 ). Common beans are high in protein and low in fats, sodium and calories ( Celmeli et al, 2018 ; Kibar and Kibar, 2019 ).…”
Section: Introductionmentioning
confidence: 99%